Analysis of a centreline failure of a lead alloy anode used in the copper electro-winning process. (February 2021) - Elrefaey, A.; Gu, Y.; James, J.D.; Kneen, C.; Crabbe, I.; Sienz, J.
Highlights: Corrosion attack and propagation were surprisingly at the centre of the lead anode. Extensive rolling of the anode is probably the main reason for exfoliation corrosion. Manganese contaminated electrolyte is deteriorating to the anode corrosion resistance. The lead anode alloy was prone to exfoliation corrosion. Methods were suggested to overcome the reason of failure. Abstract: Thousands of lead anodes are currently used in the electro-winning of copper across the globe. The corrosion and the electrochemical performance of these anodes significantly affect the economy of the process. Premature failure of anodes is often a problem for the commercial operators of tank houses. Recently, the authors were asked to advise on an unusual case where a lead alloy anode split at almost the centreline of the cross section. Different characterization techniques were employed to detect the cause of failure. The fractured samples were metallographically examined with an optical microscope and a Scanning Electron Microscope (SEM) equipped with Energy-Dispersive X-ray Spectroscopy (EDS) analysis. Different phase at the fracture surface were also identified by X-Ray Diffraction technique. The failure mechanism of this anode appears to be manganese contaminated electrolyte attacking the anode perimeter, leading to initial corrosion sites and compounded by subsequent exfoliation corrosion through inter-granular attack and further formation of manganese dioxide. The established practice of producing lead alloy anodes via rolling confers beneficial properties to the finished anodes. However, the resulting elongated grains can in some cases, where the electrolyte is contaminated with elements that are prejudicial to stable oxide layer formation, cause susceptibility to exfoliation corrosion.